Design of an On-line Library Cataloguing System. - Faleye, Emmanuel Omoniyi (Obafemi Awolowo University, 2014)
The work reported in this thesis is on the design of a portable on-line library cataloging system (including serials' cataloging and binding subsystem) for possible implementation at the University of Ife library.